HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KINERJA PERAWAT DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RSUD DR. MM. DUNDA LIMBOTO KABUPATEN GORONTALO TAHUN 2013 - Firmawati Firmawati; Thamrin Kum (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The implementation of nursing care documentation is determined by behavioral approach This behavioral approach is used in providing nursing care by considering the aspect of human behavior, e.i. the internal factors owned by the nurse, including knowledge and attitudes. The purpose of this study was to determine the relationship between knowledge and attitudes of the nurses with nurses performance in nursing care documentation in Dr. MM. Dunda Hospital, Limboto, Gorontalo Regency. The study design used was Cross - Sectional with sample of 87 respondents. In Cross-Sectional Research, the researchers conducted observation on nursing care documentation in the medical record room of Dr. MM Dunda Hospital, Limboto. As for the knowledge and the attitudes of the nurses were measured only once in the treatment room of Dr. MM Dunda Hospital, Limboto. The result showed that respondents with less knowledge level was 51.7%, the nureses which have good attitude showed 52.9% and the nurses who have less performance were 50.6%. In addition, this study also shows that there is a significant relationship between knowledge and attitude of the nurses in documenting nursing care with the performance of the nurses. Based on the results of this study, the Nurses Department is expected to hold a refreshing treatment in nursing care documentation. Also to conduct trainings and workshops on nursing documentation standards and to increase the knowledge of the nurses in nursing documentation.